Estimates for wavelet coefficients on some classes of functions
Let ψ_m^D be orthogonal Daubechies wavelets that have m zero moments and let W^k_2, p = {f L_2(R): ||(i ω)^k f(ω)||_p ≤ 1}, k N,. We prove that _m→∞{|ψ^D_m, f|||(ψ^D_m)^||_q: f W^k_2, p } = (2π)^1/q-1/2 π^k(1 - 2^1-pk pk -1)^1/p (2π)^1/q-1/2 ., number=12, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Babenko, V. F. and Spector, S. A., year=2007, month=Dec., pages=1594–1600